Validation of Previous Spirometric Reference Equations and New Equations - Choi, Hye Sook (J Korean Med Sci, 2019)
BACKGROUND: Pulmonary functions are interpreted using predicted values from reference equations that vary with ethnicity, gender, age, height, and weight. The universally used Choi's reference equations are not validated for Korean populations, and the purpose of this study was to validate them and develop new reference equations. METHODS: Subjects with normal spirometry and chest radiographs, no co-morbidities, and non-smokers, from the Korean National Health and National Examination Survey (KNHANES)-VI were enrolled (n = 117). Intraclass correlation coefficient (ICC) was assessed for reliability of reference equations. New reference equations were developed using linear regression analysis. Differences between observed and predicted values were assessed to compare the reference equations from Choi's, Global Lung Function Initiative 2012, KNHANES-IV, and newly developed equations. RESULTS: The ICC of Choi's reference equations was 0.854 (P < 0.001). The new reference equations for men were: forced vital capacity (FVC) (L) = − 4.38775 − 0.01184 × age + 0.05547 × height, forced expiratory volume – 1 second (FEV(1)) (L) = − 2.40147 − 0.02134 × age + 0.04103 × height; and for women: FVC (L) = − 3.09063 + 0.003904 × age + 0.038694 × height; FEV(1) (L) = − 1.32933 − 0.00872 × age + 0.02762 × height. The differences between the predicted and observed means were largest in Choi's equations, but lowest in the new equations with highest goodness of fit. CONCLUSION: Because Choi's reference equations presented larger differences from the observed values, despite reliability, and the new reference equations showed better goodness of fit, we suggest the latter for Korean populations.